Analysis and modelling composite timber-concrete systems: Design of bridge structure according to EN - Manojlović Dragan (Građevinski Materijali i Konstrukcije, 2016)
Timber-concrete composite structures are already applied more than 80 years in engineering practice, went trought the intuitive problem solution to the fully prefabricated hybride assemblies for dry building. The development path of timber-concrete composites was always followed by extensive theoretical and experimental research, whose results were successfully implemented in practice, i.e. on the market, but till presence didn't result in modern designer's code. In expectation of new European codes for timber-concrete composites, the objective of the paper is to provide a comprehensive review of available standards provisions and recent conclusions from literature. The key issues for practical design are highlighted and ilustrated on the example of glulam composite arch bridge structure with concrete deck, according the Eurocodes.